دور الصور في تعليم المفردات والتراكيب العربيّة للناطقين بغيرها (The usage of pictures in teaching vocabularies and Arabic structural sentences to the non - native speakers of Arabic) - (Saupi Bin Man al-Ummah), صوفي بن مان الأمـة; (Rohaizaf Mizani Bin Mat Zain), روحيزاف ميزاني بن مت ز (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: تهدف هذه الدراسة إلى عرض الخبرة السابقة في تعليم المفردات والتراكيب والجمل باستخدام الصور التعليمية للطلبة الناطقين بغير العربية، وأن الصور التعليمية تؤدي دورا كبيرا في تدريب الطلبة على التعبير الحر والتعبير المقيد، وتهدف إلى ذكر خطوات التدريس المتبعة التي يرى فيها الباحثان نجاح برنامج الخبرة السابقة بصورة مقنعة، وأن الطلبة قادرون على التعبير عن الصور المدروسة بصورة مقبولة جدا ومناسبة بمستواهم التعليمي والعمري. ومن نتائج هذه الدراسة أن ثمة ضرورة في تعليم اللغة العربية للناطقين بغيرها عن طريق الصور التعليمية؛وأهمية دور المعلم في مناقشة المفردات، ووصف الصورة، ويتعلم الدارسون مهارة الاستماع عن طريق مناقشة المعلم شفاهة، ويتعلم الدارسون مهارة الكلام عبر الممارسة اللغوية التي يقومون بها في الأنشطة التعليمية. الكلمات المفتاحية: فرضية الدراسة-الصور التعليمية-التجربة-التدريس-الكتابة Abstract: This research aims to present previous experiences in teaching vocabularies and structural sentences with the usage of pictures to the non - native students of Arabic. The use of pictures has a significant role in training students in making expressions. The research also aims to point out the teaching steps that were successful in the view of the two researchers as students were able to make expressions based on the pictures in an accepted way and in the manner suitable to their level of studies and age. The findings of this research show that there is a necessity in teaching non - native speakers of Arabic Language with the use of pictures. The role of teachers in discussing vocabularies and explaining the pictures is also highly significant since the students will be able to acquire listening skills from the discussion of the teacher verbally. Furthermore, they also will be able to learn conversation skills by practicing the language in the activities that are carried out. Keywords: Hypothesis of the research – Pictures – Experiment –Teaching – Writing Abstrak: Kajian ini bertujuan mendedahkan pengalaman dalam pengajaran kosa kata serta ayat-ayat dalam bahasa Arab dengan menggunakan gambar-gambar pendidikan kepada pelajar bukan penutur berbahasa Arab. Sesungguhnya gambar-gambar pendidikan memainkan peranan besar dalam melatih pelajar tentang pernyataan bebas serta pernyataan berkait. Kajian ini juga bertujuan menyatakan langkah-langkah pengajaran yang diikuti yang dilihat oleh para pengkaji sebagai berjaya dan berkesan. Para pelajar didapati berupaya mengemukakan pernyataan tentang gambar-gambar yang telah dipelajari dengan baik bersesuaian dengan tahap pembelajaran dan usia masing-masing. Antara dapatan kajian ialah terdapat keperluan terhadap cara pengajaran bahasa Arab kepada bukan penutur berbahasa Arab dengan menggunakan gambar pendidikan, kepentingan peranan guru dalam membincangkan kosa kata dan menerangkan gambar di mana pelajar dapat menguasai kemahiran mendengar melalui perbincangan secara lisan, seterusnya menguasai kemahiran bertutur melalui amalan bahasa semasa melaksanakan aktiviti-aktiviti pengajaran. Kata kunci: hipotesis kajian – gambar-gambar pendidikan – pengalaman – pengajaran - penulisan